The role of anion gap normalization time in the management of pediatric diabetic ketoacidosis - Lazar, Isaac; Wizeman-Orlov, Dorit; Hazan, Guy; Orbach, Asaf; Haim, Alon; Cavari, Yuval; Feinstein, Yael; Neeman, Eitan; Hershkovitz, Eli; Faingelernt, Yaniv (Frontiers in Pediatrics, 2023)
Introduction: To determine whether anion gap normalization time (AGNT) correlates with risk factors related to the severity of diabetic ketoacidosis (DKA) in children, and to characterize AGNT as a criterion for DKA resolution in children admitted with moderate or severe disease. Methods: A ten-year retrospective cohort study of children admitted to intensive care unit with DKA. We used a survival analysis approach to determine changes in serum glucose, bicarbonate, pH, and anion gap following admission. Using multivariate analysis, we examined associations between patients’ demographic and laboratory characteristics with delayed normalization of the anion gap. Results: 95 patients were analyzed. The median AGNT was 8 hours. Delayed AGNT (>8 hours) correlated with pH <7.1 and serum glucose >500mg/dL. In multivariate analysis, glucose >500mg/dL was associated with an increased risk for delayed AGNT, by 3.41fold. Each 25 mg/dL elevation in glucose was associated with a 10% increment in risk for delayed AGNT. Median AGNT preceded median PICU discharge by 15 hours (8 vs. 23 hours). Discussion: AGNT represents a return to normal glucose-based physiology and an improvement in dehydration. The correlation observed between delayed AGNT and markers of DKA severity supports the usefulness of AGNT for assessing DKA recovery.